2021
DOI: 10.1049/cit2.12017
|View full text |Cite
|
Sign up to set email alerts
|

Accurate detection method of pig's temperature based on non‐point source thermal infrared image

Abstract: Body temperature measurement is a very important task in the sow breeding process. The authors used an infrared camera to detect the temperature of the body surface of the sows, relying on calculating the average of the infrared image temperature in the ear root region. Based on the grayscale value of the target image of the infrared image and the corresponding temperature value of 180 infrared images, a G‐T (Gray‐Temperature) model was established by linear least squares method, which achieved temperature inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Stukelj et al (4) , however, established three anatomical regions in healthy pigs: the ear canal, the outer ear, and the perianal region, for predicting the body temperature. Zhang et al (28) , observed high association between rectal temperature and the base of the ear. Similar, Schmitt & O'Driscoll (22) in their study, rectal temperature was correlated with all infrared thermography (IRT) data and found correlations were strongest with the ear base, and weakest with the ear tip and minimum back temperature.…”
Section: Resultsmentioning
confidence: 98%
“…Stukelj et al (4) , however, established three anatomical regions in healthy pigs: the ear canal, the outer ear, and the perianal region, for predicting the body temperature. Zhang et al (28) , observed high association between rectal temperature and the base of the ear. Similar, Schmitt & O'Driscoll (22) in their study, rectal temperature was correlated with all infrared thermography (IRT) data and found correlations were strongest with the ear base, and weakest with the ear tip and minimum back temperature.…”
Section: Resultsmentioning
confidence: 98%
“…In recent years, a large number of researches have been conducted to detect the temperature of the pig-body, which is an important physiological indicator in many applications such as the early diagnosis and treatment diseases [7], [11], [14], [17]. To date, pig body temperature measurement techniques can be classified into two group, namely: i) contact; and ii) non-contact [5].…”
Section: Related Workmentioning
confidence: 99%
“…However, this technique still has some limitations, such as high initial investment cost, does not tend to work well underwater, can not detect radiation through glass, and especially the accurate temperature measurements are hindered by surrounding infrared sources. In order to improve the performance of the IRT method and to eliminate the influence of ambient temperature on temperature detection, some studies have focused on using infrared image processing techniques to detect target objects [17], [20]- [22]. In the context of various illumination conditions, Sa et al by their work [20] represented a pig monitoring strategy, in which the complementary information from depth and infrared images is exploited for pig detection.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, noninvasive data collection or monitoring is the safest method for humans since the interaction between humans and animals can cause infection to pass from animals to humans or humans to animals. Generally, any infection causes weakness [ 114 ], fever [ 9 , 116 ], and progressive deceleration of diurnal activities [ 67 ]. Monitoring activities such as drinking, eating, lying, and walking is significant, and changes in activities are a way to track animal health.…”
Section: Early Disease Detection At a Farm Levelmentioning
confidence: 99%